DIW 3D printing of hybrid magnetorheological materials for application in soft robotic grippers. (26th May 2022) - Guan, Ruihua; Zheng, Hengyu; Liu, Qingxiao; Ou, KangTai; Li, Dian-sen; Fan, Jiang; Fu, Qiang; Sun, Youyi
Abstract: A new hybrid magnetorheological material is prepared by DIW 3D printing technology, which is composed of magnetorheological fluid and magnetorheological elastomer. It does not only exhibit high magnetorheological effect of magnetorheological fluid, but also shows high mechanical stability of magnetorheological elastomer. The maxima absolute and relative magnetorheological effect of hybrid magnetorheological material are about 11.1 MPa and 7474%, which are simultaneously improved to be 2.9 times and 7.8 times comparing to single magnetorheological elastomer. Furthermore, the hybrid magnetorheological material is evaluated for application in soft robotic grippers. It shows larger clamping force (7.0 × 10 −3 N) and faster response rate (ca.2.0s) comparing to other actuators. The work provides a new method to prepare hybrid magnetorheological material with high performance for various applications. Graphical abstract: Image 1